Assessment of Financial Reporting on Investment Decision of Deposit Money Bank in Nigeria - Charles, J. Mambula I.; Francis, Felix; Zirra, Clifford Tizhe Oaya (Archives of Business Research, 2023)
Most business organizations require some measures of both financial position and financial performance in assessing its financial conditions. The study thus examines financial reporting on investment decision of deposit money bank in Nigeria. Descriptive research design was adopted, while Pearson Chi square was used in testing the hypothesis. Findings from the study showed that financial reporting has effect on investment decision-making money deposit bank. More so, the study revealed that financial reporting has revealed the competence of management of organization. The study also revealed there is a relationship between financial reporting and investment decision-making. The study thus recommends effectively competence of management of organization contributes to the efficiency of financial reporting. This will ensure that various companies’ financial reports are properly managed.